Combating Climate Change in the Kenyan Tea Industry - Muoki, Chalo Richard; Maritim, Tony Kipkoech; Oluoch, Wyclife Agumba; Kamunya, Samson Machohi; Bore, John Kipkoech (Frontiers in Plant Science, 2020)
Climate change triggered by global warming poses a major threat to agricultural systems globally. This phenomenon is characterized by emergence of pests and diseases, extreme weather events, such as prolonged drought, high intensity rains, hailstones and frosts, which are becoming more frequent ultimately impacting negatively to agricultural production including rain-fed tea cultivation. Kenya is predominantly an agricultural based economy, with the sector generating about 26% of the total export earnings and about 4% gross domestic product (GDP). In the recent years however, the country has witnessed unstable trends in tea production associated with climate driven stresses. Towards mitigation and adaptation of climate change, multipronged approaches for impact assessment, intensity prediction and adaptation have been advanced in the Kenyan tea sub-sector. Further, pressure on tea breeders to release improved climate-compatible cultivars for the rapidly deteriorating environment has resulted in the adoption of a multi-targeted approach seeking to understand the complex molecular regulatory networks associated with biotic and abiotic stresses adaptation and tolerance in tea. Genetic modelling, a powerful tool that assists in breeding process, has also been adopted for selection of tea cultivars for optimal performance under varying climatic conditions. A range of physiological and biochemical responses known to counteract the effects of environmental stresses in most plants that include lowering the rates of cellular growth and net photosynthesis, stomatal closure, and the accumulation of organic solutes such as sugar alcohols, or osmolytes have been used to support breeding programmes through screening of new tea cultivars suitable for changing environment. This review describes simulation models combined with high resolution climate change scenarios required to quantify the relative importance of climate change on tea production. In addition, both biodiversity and ecosystem based approaches are described as part of an overall adaptation strategy to mitigate against adverse effects of climate change on tea in Kenya and gaps highlighted for urgent investigations.